The effect of problem-based learning model on mathematical communication ability of junior high school students on the material of flat-sided space building - Haryanza, Ajeng Sucitra; Pradipta, Trisna Roy (Universitas Islam Negeri Raden Intan Lampung, 2023)
This study was influenced by the low mathematical communication of students due to the learning system that still uses the traditional system. The application of the problem-based learning (PBL) model is very important. This research is based on a quantitative approach using a quasi-experimental type with a planning framework of a non-equivalent control group design and a post-test only. The population of this study was VIII-grade students at SMPIT AT-Taufiq in the 2022–2023 school year. The sample consisted of 26 students who received treatment (experimental class) and 25 students who did not receive treatment (control class). The information storage strategy is carried out using a written mathematical communication ability test tool of 7 questions with 3 indicators. The Mann-Whitney U test was used for hypothesis testing, and data analysis strategy was used to determine the effect of the problem-based learning (PBL) model on communication skills using effect size. This study resulted in a significance value of 0.000 <0.05, with 87% in the high category. Students who received the problem-based learning (PBL) treatment had a mean score of 88 compared to 75 for students who did not receive the treatment. In this study, we found that problem-based learning (PBL) for materials has an impact on the competence of the problem-based learning (PBL) model on students' mathematical communication skills.